2018
DOI: 10.1177/2054358118809974
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Left Ventricular Characteristics Assessed by Cardiac Magnetic Resonance Imaging and Cardiovascular Biomarkers Related to Kidney Transplantation

Abstract: Background:Cardiac magnetic resonance (CMR) imaging accurately and precisely measures left ventricular (LV) mass and function. Identifying mechanisms by which LV mass change and functional improvement occur in some end-stage kidney disease (ESKD) patients may help to appropriately target kidney transplant (KT) recipients for further investigation and intervention. The concentration of serum adiponectin, a cardiovascular biomarker, increases in cardiac failure, its production being enhanced by B-type natriureti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 47 publications
2
37
0
1
Order By: Relevance
“…In the CMR evaluation, considering ventricular function, volume and mass, we did not find differences at 6 months, similar to Patel [34] and Prasad et al [35]. Patel performed the first study to serially evaluate the LVs of patients who have undergone kidney transplantation using CMR.…”
Section: Discussionsupporting
confidence: 86%
“…In the CMR evaluation, considering ventricular function, volume and mass, we did not find differences at 6 months, similar to Patel [34] and Prasad et al [35]. Patel performed the first study to serially evaluate the LVs of patients who have undergone kidney transplantation using CMR.…”
Section: Discussionsupporting
confidence: 86%
“…The recruitment of participants for this study has been described [14, 13]. The study sample size target of 42 subjects per group was designed to detect a 5 µg/ml change in adiponectin, with expected attrition of 20%.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported the left ventricular changes in patients on dialysis receiving a kidney transplant. While both left ventricular volume and adiponectin levels decreased with a kidney transplant, the change in adiponectin level and the change in HDL cholesterol were not associated with the change in left ventricular volume [13]. CMR is, therefore, a useful tool to correlate biomarker changes after transplantation with measurable changes in cardiac function.…”
Section: Introductionmentioning
confidence: 99%
“…All three CMR studies reported no significant overall change in LVMI. [48][49][50] However, the trends in mean change were conflicting. Patel et al 49 observed an increase in LVMI in transplant recipients and a decrease in the control group of haemodialysis patients (À3.6 ± 16.7%/year vs. 2.75 ± 9.1%/year).…”
Section: Left Ventricular Mass Indexmentioning
confidence: 99%